The contribution of an academic league in undergraduate teaching in nursing - Marislei Sanches Panobianco; Mariana Lopes Borges; Edilaine Assunção Caetano; Bárbara Alexandre Lespinassi Sampaio; Paola Alexandria Pinto de Magalhães; Débora Cherchiglia de Moraes (Rev Rene)
This quantitative, descriptive and cross study, which aimed to identify and assess the contribution of the Students’ League in the education undergraduate nursing. Data were collected from May to August 2010, using a semi-structured questionnaire, applied to graduate students on the premises of an institution of higher education and sent via electronic mail, to the graduates, a total of 22 respondents linked to a league preventing and combating cancer. The answers were structured in a database in Excel (Windows 2007), and after, the analysis performed by means of Epi Info software, using descriptive statistics. Respected the ethical rules. All respondents said that the league has contributed to academic learning. The League proved to be an important educational strategy, contributing to training to critical reflection on oncology and promoting humane care.